The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/bimj.201700203
|View full text |Cite
|
Sign up to set email alerts
|

Testing random effects in linear mixed‐effects models with serially correlated errors

Abstract: In linear mixed‐effects models, random effects are used to capture the heterogeneity and variability between individuals due to unmeasured covariates or unknown biological differences. Testing for the need of random effects is a nonstandard problem because it requires testing on the boundary of parameter space where the asymptotic chi‐squared distribution of the classical tests such as likelihood ratio and score tests is incorrect. In the literature several tests have been proposed to overcome this difficulty,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As a consequence, there is no open set containing the true variance components under the null hypothesis. Therefore, the classical asymptotic chi-squared distribution of the likelihood ratio (LR) or restricted LR test statistic is not valid (see, for example, Stram and Lee, 1994;Drikvandi et al, 2012Drikvandi et al, , 2013Drikvandi and Noorian, 2019). For testing zero variance components, it is shown that the correct asymptotic distribution of the LR or restricted LR statistic is a mixture of chi-squared distributions, provided that the response variable can be partitioned into independent subvectors and the number of subvectors tends to infinity (e.g., Stram and Lee, 1994).…”
Section: Testing For a Polynomial Fit Versus A Penalised Spline Smoothermentioning
confidence: 99%
“…As a consequence, there is no open set containing the true variance components under the null hypothesis. Therefore, the classical asymptotic chi-squared distribution of the likelihood ratio (LR) or restricted LR test statistic is not valid (see, for example, Stram and Lee, 1994;Drikvandi et al, 2012Drikvandi et al, , 2013Drikvandi and Noorian, 2019). For testing zero variance components, it is shown that the correct asymptotic distribution of the LR or restricted LR statistic is a mixture of chi-squared distributions, provided that the response variable can be partitioned into independent subvectors and the number of subvectors tends to infinity (e.g., Stram and Lee, 1994).…”
Section: Testing For a Polynomial Fit Versus A Penalised Spline Smoothermentioning
confidence: 99%
“…Again, care ought to be taken when calculating the caught variance with associated or correlated loadings. Note that assessing and testing a significant variance in correlated models is a nonstandard testing problem [11][12][13][14].…”
Section: Correlation Of Loadingsmentioning
confidence: 99%
“…More recently, this approach has been considered by several authors in conjunction with empirical Bayesian and permutation test (e.g. [24]) while Drikvandi and Noorian [7] have considered the permutation test for a more broad class of linear mixed models with correlated errors. The results were shown that both tests to perform well, albeit the permutation test with the likelihood ratio statistic tends to provide a relatively higher power when testing multiple random effects.…”
Section: Introductionmentioning
confidence: 99%